2006
DOI: 10.1128/aem.00161-06
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence In Situ Hybridization-Flow Cytometry-Cell Sorting-Based Method for Separation and Enrichment of Type I and Type II Methanotroph Populations

Abstract: A fluorescence in situ hybridization-flow cytometry (FISH/FC)-based method was optimized using artificial mixtures of pure cultures of methanotrophic bacteria. Traditional oligonucleotide probes targeting 16S rRNAs of type I (MG84/705 probe) and type II (MA450 probe) methanotrophs were labeled with fluorescein or Alexa fluor and used for FISH, followed by fluorescence-activated FC analysis and cell sorting (FACS). The method resulted in efficient separation of target cells (type I or type II methanotrophs) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 46 publications
2
87
1
2
Order By: Relevance
“…Reducing bacterial DNA template from 10 ng (410 6 genome copies) by 10-and 100-1000-fold reduced representational bias 3-and 6-fold, respectively (Wu et al, 2006). Other studies also showed increased bias with decreased template copy number (Detter et al, 2002;Bergen et al, 2005;Holbrook et al, 2005;Kalyuzhnaya et al, 2006;Neufeld et al, 2008).…”
Section: A Brief History Of Mdamentioning
confidence: 94%
See 1 more Smart Citation
“…Reducing bacterial DNA template from 10 ng (410 6 genome copies) by 10-and 100-1000-fold reduced representational bias 3-and 6-fold, respectively (Wu et al, 2006). Other studies also showed increased bias with decreased template copy number (Detter et al, 2002;Bergen et al, 2005;Holbrook et al, 2005;Kalyuzhnaya et al, 2006;Neufeld et al, 2008).…”
Section: A Brief History Of Mdamentioning
confidence: 94%
“…Even partial genomic drafts from single cells provide genetically linked sequences useful for guiding the assembly of metagenomic sequences into discrete genomes (Lasken, 2007). In a proof of principle for community analysis, cells from a defined mixture of three methylotrophic bacteria were separated by flow sorting (Kalyuzhnaya et al, 2006) using 16S rRNA FISH probes that distinguished between these three methylotrophs. When 10 1 , 10 2 and 10 3 cells were collected in each tube and subjected to MDA, 20%, 50% and 95% of resulting DNA sequences correctly associated with the FISH-targeted organism, and none were from the 'contaminating' organisms; the remaining sequences corresponded to nonspecific DNA synthesis generated as an artifact of MDA.…”
Section: Use Of Mda In Microbial Ecologymentioning
confidence: 99%
“…Aerobic MOB have been detected in a variety of environments, and in some they represent significant fractions of total microbial communities (e.g. Henckel et al 1999;Carini et al, 2005, Trotsenko & Khmelenina 2005, Kalyuzhnaya et al 2006. However, the data on the diversity and activity of methanotrophic communities from the river ecosystems are yet fragmentary.…”
Section: Introductionmentioning
confidence: 99%
“…Kalyuzhnaya et al (62) used this approach to examine methanotrophic bacteria from lake sediments and Sekar et al (63) used similar methods to investigate the composition of marine bacterioplankton communities. Post-sorting genomic techniques were used in both cases for additional sample characterization (62,63). Food applications of FISH-FC include the use of a Pseudomonas-specific DNA probe to detect this spoilage organism in milk (64) and detection of Salmonella spp.…”
Section: Combining Fish and Flow Cytometrymentioning
confidence: 99%